FACTORS AFFECTING VISITORS’ ATTRIBUTES TO THEME FARMS IN TAIWAN - WEN -HWA KO (ASEAN Journal on Hospitality and Tourism, 2008)
This study examines consumption patterns, attributes, and consumer satisfaction in visiting theme farms in Taiwan. Four hundred and fifty questionnaires were distributed and 432 completed questionnaires returned. Descriptive, factor analysis and regression analysis is used in this study. Base on the results, only 55.9 % of respondents visit a theme farm at least once in the past year. They spend 2 to 6 hours at the theme farm. They prefer to be accompanied by family and friends when they visit the theme farm. Factor analysis results indicate that the underlying factors consumers’ attribute when they select theme farms includes: experience, education, and extensibility. Visitor satisfaction has the most effect on the attribute factors of experience and education as shown by the regression analysis.